Sosialisasi Pencegahan Penyalagunaan NAPZA dengan Edukasi Dampak Negatif NAPZA terhadap Remaja Karang Taruna Tanjung Pinang l - Mutia Mawardah; Mistriyanti Mistriyanti; Susan Dian Purnamasari; Nia Oktaviani; Fatmasari Fatmasari (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Drug abuse (narcotics, psychotropics and other addictive substances) is a serious problem that can threaten physical, mental and social health, especially in adolescents. This outreach program aims to provide education about the negative impacts of drug abuse on teenagers at Karang Taruna Tanjung Pinang. The method used is the delivery of educational material and outreach. The results of this program show an increase in participants' understanding of the dangers of drugs. Thus, this outreach not only contributes to prevention efforts at the community level but also becomes a model that can be adapted for similar prevention programs in various regions.